Yahoo! hacks - Bausch, Paul (Hacks series., 2005)
Yahoo! took the world by storm in the 1990s as a one-of-a-kind, searchable list of interesting web sites. But ten years later, it has expanded into a department store overflowing with useful and innovative tools and services-from email, blogging, social networking, and instant messaging, to news, financial markets, shopping, movie and TV listings, and much more. Today's Yahoo! keeps you connected with every aspect of your life and every corner of the Web. Yahoo! Hacks shows you how to use, expand, personalize, and tweak Yahoo! in ways you never dreamed possible. You'll lea.